Bidirectional Association Between Sleep and Brain Atrophy in Aging - Kokošová, Viktória; Filip, Pavel; Kec, David; Baláž, Marek (Frontiers in Aging Neuroscience, 2021)
Human brain ageing is characterized by the gradual deterioration of its function and structure, affected by the interplay of a multitude of causal factors. Namely, sleep, a periodically repeating state of reversible unconsciousness characterised by distinct electrical brain activity, is crucial for maintaining the brain homeostasis. Indeed, insufficient sleep was associated with accelerated brain atrophy and impaired brain functional connectivity. Concurrently, alteration of sleep-related transient electrical events in senescence correlated with structural and functional deterioration of brain regions responsible for their generation, implying the interconnectedness of sleep and brain structure. This review discusses currently available data on the link between human brain ageing and sleep derived from various neuroimaging and neurophysiological methods. We advocate the notion of a mutual relationship between the sleep structure and age-related alterations of functional and structural brain integrity, pointing out the position of high-quality sleep as a potent preventive factor of early brain ageing and neurodegeneration. However, further studies are needed to reveal the causality of the relationship between sleep and brain ageing.